Dynamics and grain orientation dependence of the electric field induced phase transformation in Sm modified BiFeO3 ceramics. Issue 28 (6th July 2018) - Ormstrup, Jeppe; Makarovic, Maja; Majkut, Marta; Rojac, Tadej; Walker, Julian; Simons, Hugh
Abstract : Sm-Modified BiFeO3 multiferroic ceramics experience two simultaneous electric field induced phase transformations, both of which have strong grain orientation dependences and slow transformation kinetics in the order of several minutes. Abstract : Samarium-modified bismuth ferrite ((Bi, Sm)FeO3 or BSFO) is a room-temperature multiferroic with a morphotropic phase boundary near 15.5 mol% Sm, where ferroelectric, antiferroelectric and paraelectric phases coexist and the electromechanical response ( S max / E max and d 33 ) is maximized. Recently, an electric field induced phase transformation was discovered, which is believed to play a significant role in the macroscopic electromechanical response. Here, we used in situ synchrotron X-ray powder diffraction to directly measure this transformation in real time within bulk ceramics to determine the dynamics, structural pathway and crystallographic orientation dependence of the transformation. Our results show that there are two transformation pathways; an antiferroelectric-to-ferroelectric transformation, which is revesible, and a paraelectric-to-ferroelectric transformation, which is irreversible. Furthermore, these transformations occur with a strong orientation dependence with respect to the applied electric field direction, and with extremely slow dynamics – just 2 to 10 minutes – orders of magnitude longer than in other ferroelectrics ( e.g. Bi1/2 Na1/2 TiO3 –BaTiO3 or BNT–BT). These findings point to texturing and the elimination of the paraelectric phase to enhance the electromechanical response. Moreover, they provide a detailed picture of the transformation dynamics and a greater understanding of electric field induced transformations in ferroelectric ceramics.